Impact of soil and water conservation intervention on soil physico-chemical properties in Awash Basin, Ethiopia - Alebachew Shumye Moges; Sisay Assefa Wondimagegn (Soil Security)
Since 2010, soil and water conservation practices have been implemented throughout the Dawule watershed to restore its degraded landscape. However, a comprehensive evaluation of these conservation measures' effects on soil physico-chemical properties has not been conducted. This study assessed the influence of conservation interventions on soil characteristics within the watershed.The research examined various land use types (enclosures, cultivated land, open grazing land, and bare land) and conservation approaches (physical and biological) across three slope gradients (gentle, medium, and steep). Non-conserved areas with comparable slope classifications were included as controls. Soil analysis employed a two-way ANOVA design. Thirty-six soil samples were collected at 0–30 cm depth from each land use type for laboratory analysis, and 208 households were surveyed to evaluate conservation practices' impact on land productivity, erosion control, runoff reduction, and sediment retention.Results demonstrated significant variations in soil physical properties (bulk density, moisture content, and texture) between conserved and non-conserved areas. Chemical properties—including pH, electrical conductivity, exchangeable potassium, cation exchange capacity, organic carbon, organic matter, and available phosphorus—showed significant differences across land management types and slope positions (p < 0.05). Areas managed with stone-face soil bunds exhibited particularly significant improvements in soil physico-chemical properties (p < 0.05).Additionally, most respondents reported decreased soil erosion rates and increased land productivity following the implementation of conservation practices. These findings highlight the importance of appropriate conservation measures for reducing soil loss, enhancing soil physical and chemical properties, and improving overall land productivity in the watershed.